Supply Chain Management: A Global Perspective - Nada R. Sanders (USA, 2012)
In Supply Chain Management 1e, Nada Sanders presents material from a uniquely balanced, integrative, and business-oriented viewpoint. Examining supply chain management as a boundary-spanning function that is intertwined with other organizational areas, the text provides future supply chain managers instruction on interactions and integration of multiple business units. Supply Chain Management contains extensive pedagogy and solved problems to make difficult concepts accessible, along with examples of the latest business practices in supply chain management.
Keywords: Business logistics; Nonfiction; (MASB-3111) Logistics and supply chain management